A Summary Sentence Decomposition Algorithm for Summarizing Strategies Identification - Idris, N.; Baba, S.; Abdullah, R. (2009)
Expert summarizers employ a number of strategies to produce summaries. Teachers need to identify which strategies are used by students to help them improve their summary writing. However, the task is time consuming. This paper reports on our effort to develop an algorithm to identify the summarizing strategies employed by students using summary sentence decomposition. The summarizing strategies used by experts are identified and translated into a set of heuristic rules. A summary sentence decomposition algorithm is then developed based on the heuristic rules. A preliminary test was carried out and the results are discussed.